Sustainability and corporate governance mechanisms in mexican beef production (2022)
Sustainability is a topic that has experienced a growing interest in recent years within the academic world, and at the same time, it manifests itself as a particular inconsistency of the business sector, who use it as a means to improve their image, setting aside its vision of great significance. In order to achieve the fundamental purpose of sustainability, the corporate governance model has been an evolving subject in recent years. This is due to the fact that even though the mechanism still endures, it has little to do with the balance of social and environmental benefits. In Mexico, cattle ranchers have faced several problems, such as the difficulty of marketing with intermediaries. In response, this quantitative study has been carried out in order to identify a possible relationship between sustainability and corporate governance, through the testing of six hypotheses. The findings show a positive correlation between corporate governance mechanisms (formal and efficiency) and sustainability dimensions (economic, social, and environmental). This provides further evidence of the complexity of sustainability and corporate governance issues.